Clinical and Experimental Evidence of Hypoglycemic Neuropathy - Yung-Chu Hsu; Hui-Lun Zhan; Chun-Pai Yang (Diabetes Research, 2015)
When compared with the extensive research on hypoglycemic impacts on Central Nervous System (CNS) and cardiovascular system, the effects of hypoglycemia on the Peripheral Nervous System (PNS) have not been investigated as thoroughly. Epidemiologic data and risk factors for hypoglycemic neuropathy are still lacking. Interestingly, hyperglycemia mainly results in the damage of sensory and autonomic nerve fibers, whereas hypoglycemia predominantly leads to the development of motor neuropathy. Most clinical features are concluded from patients with insulinoma, and neuropathology has shown axonal degeneration in large myelinated fibers. Experimental animal models support the clinical and histopathological findings. The exact pathophysiological mechanisms of hypoglycemic neuropathy remain elusive. The influence of hypoglycemia on peripheral nervous system warrants further investigations.